Anti-Cancer Activity Testing of Cumin (Plectranthus Amboinicus) Ethanol Extract Against Artemia Salina Leach by Using Brine Shrimp Lethality Test (BSLT) Method - ika Rachutami; Rahma Diyan Martha; Afidatul Muadifah; Algafari Bakti Manggara (Walisongo Journal of Chemistry, 2022)
The purpose of this study was to determine the anticancer activity of cumin leaf extract (Plectranthus amboinicus), which was applied using the Brine Shrimp Lethality Test (BSLT) method to determine the level of acute toxicity (LC50) of the extract against Artemia salina LEACH larvae. Cumin leaf samples were extracted using the maceration method with 96% ethanol. The cumin leaf extract was then tested qualitatively and quantitatively. Toxicity testing used concentrations of 500 ppm, 1000 ppm, 1500 ppm, 2000 ppm, and 2500 ppm, which were given to Artemia salina LEACH larvae for 24 hours. Calculate the LC50 value in this study using probit analysis. The results of qualitative and quantitative testing showed the presence of saponins by 5.20%, tannins by 8.21%, flavonoids by 23.93%, and alkaloids by 4.37%. The results of the acute toxicity test of the extract using the BSLT method showed that there was anticancer activity with the acquisition of LC50 of 1000 ppm, which was 697.99 ppm.